A closer look at 1MDB framing in Malaysian mainstream English newspapers before and after GE-14 - Ahmad, Arman; Ahmad Ghazali, Akmar Hayati; Mohd Zawawi, Julia Wirza; Yaakup, Hani Salwah (Human Resource Management Academic Research Society, 2022)
An analysis of mainstream Malaysian English newspaper coverage of the 1Malaysia Development Berhad's (1MDB) financial crisis before and after Malaysia's 2018 14th General Election is presented in this study. Content analysis was used to undertake a quantitative analysis of news stories from four mainstream English newspapers, namely The Star, New Straits Times, The Edge, and The Sun. A total of 1,362 articles were analysed for the presence of value frames of Conflict, Economic Consequences, Responsibility, Human Interest and Morality introduced by (Semetko & Valkenburg, 2000). The findings reveal that there were significant differences in the use of the five generic frames in all of the four English mainstream newspapers following General Election 14. In particular, Conflict frames were found to have declined significantly in the period following the elections. In addition, there were also statistically significant interaction effect between newspaper and main sources indicating that the influence of the political actors is more significant than the effect of the media in determining the framing of the articles. The changes raise questions on the effectiveness of Malaysia’s media reform plans which were introduced following the 14th General Election.